The Unity of Existence and the Fundamentality of Existence: A Comparative study of the Thought of Ibn ‘Arabī dan Mullā Ṣadrā - Khalid Al Walid; Tien Rohmatin; Yuminah Yuminah (Jurusan Aqidah dan Filsafat Islam Universitas Negri Sunan Gunung Djati Bandung, 2025)
This article seeks to clarify the meaning of wujūd (existence) through a focused comparison of key terminological pairs in the thought of Ibn ‘Arabī and Mullā Ṣadrā, with the aim of elucidating how unity and multiplicity can be understood without lapsing into pantheism. The study employs a qualitative, library-based approach that draws upon both primary and secondary sources. It is conducted through conceptual analysis, comparative examination of terminology, and the mapping of functional correspondences between ideas. The main findings indicate that wujūd constitutes the most concrete reality, while multiplicity appears as a gradation of intensity. At the level of functional correspondence, a‘yān ṯābitah operate as archetypal patterns that determine tajallī (divine manifestation), whereas in Ṣadrā’s framework, wujūd rābiṭ explains existential dependency as non-autonomous existence. Tajaddud al-khalq (the continual renewal of creation) is shown to align with al-ḥarakah al-jawhariyyah (substantial motion), and the ‘ālam al-mithāl (imaginal world) functions as a barzakh mediating knowledge and stitching together the spiritual and material realms. The implications of this study the purification of terminology from pantheistic reduction, the provision of a working matrix for hermeneutics, ethics, and spiritual cultivation, and the establishment of a conceptual foundation for employing imaginal epistemology. The novelty of this research lies in its limitation of scope to two pairs of terms and in the formulation of a functional correspondence between a‘yān ṯābitah and wujūd rābiṭ without conceptual identification, thereby providing an explicit and applicable map of correspondence for the dialogue between philosophy and ‘irfān